2019
DOI: 10.14260/jemds/2019/292
|View full text |Cite
|
Sign up to set email alerts
|

Study of Anthropometric Measurements, Biochemical Parameters and Hormonal Levels in Women With Pcos at a Tertiary Center of Rural Haryana

Abstract: BACKGROUND During the past decade, our understanding of pathophysiology of PCOS has undergone a remarkable evolution. Despite our familiarity with this disease, some of its fundamental characteristics remains poorly recognized and understood. The present study focuses on comprehensive knowledge about the current and emerging concepts of the PCOS such as, pathogenesis, diagnosis and better management of the syndrome. Obesity was found to be one of the important factors that contribute to the development of long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Studies suggest that women with PCOS exhibit features of the metabolic syndrome, especially dyslipidemia which is found in majority of cases. [25][26][27][28] In 2012, Xia et al proposed that LAP was a powerful index for detection of insulin resistance in nondiabetic individuals. 29 In 2009, Wiltgen et al suggested a positive association of LAP with Homeostatic Model Assessment of Insulin Resistance (HOMA) index in PCOS and postulated that it can accurately assess insulin resistance in PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that women with PCOS exhibit features of the metabolic syndrome, especially dyslipidemia which is found in majority of cases. [25][26][27][28] In 2012, Xia et al proposed that LAP was a powerful index for detection of insulin resistance in nondiabetic individuals. 29 In 2009, Wiltgen et al suggested a positive association of LAP with Homeostatic Model Assessment of Insulin Resistance (HOMA) index in PCOS and postulated that it can accurately assess insulin resistance in PCOS women.…”
Section: Discussionmentioning
confidence: 99%